3D Bioprinted Scaffolds for Tissue Repair and Regeneration - Liu, Na; Zhang, Xiaopei; Guo, Qingxia; Wu, Tong; Wang, Yuanfei (Frontiers in Materials, 2022)
Three-dimensional (3D) printing technology has emerged as a revolutionary manufacturing strategy that could realize rapid prototyping and customization. It has revolutionized the manufacturing process in the fields of electronics, energy, bioengineering and sensing. Based on digital model files, powdered metal, plastic and other materials were used to construct the required objects by printing layer by layer. In addition, 3D printing possesses remarkable advantages in realizing controllable compositions and complex structures, which could further produce 3D objects with anisotropic functions. In recent years, 3D bioprinting technology has been applied to manufacture functional tissue engineering scaffolds with its ability to assemble complicated construction under precise control, which has attracted great attention. Bioprinting creates 3D scaffolds by depositing and assembling biological and/or non-biological materials with an established tissue. Compared with traditional technology, it can create a structure tailored to the patient according to the medical images. This conception of 3D bioprinting draws on 3D printing technology, which could be utilized to produce personalized implants, thereby opening up a new way for bio-manufacturing methods. As a promising tool, 3D bioprinting can create complex and delicate biomimetic 3D structures, simulating extracellular matrix and preparing high precision multifunctional scaffolds with uniform cell distribution for tissue repair and regeneration. It can also be flexibly combined with other technologies such as electrospinning and thermally induced phase separation, suitable for tissue repair and regeneration. This article reviews the relevant research and progress of 3D bioprinting in tissue repair and regeneration in recent years. Firstly, we will introduce the physical, chemical and biological characteristics of biological scaffolds prepared by 3D bioprinting from several aspects. Secondly, the significant effects of 3D bioprinting on nerves, skin, blood vessels, bones and cartilage injury and regeneration are further expounded. Finally, some views on the clinical challenges and future opportunities of 3D bioprinting are put forward.